2006
DOI: 10.1038/sj.ejcn.1602529
|View full text |Cite
|
Sign up to set email alerts
|

Associations of iron status with dietary and other factors in 6-year-old children

Abstract: Objective: To investigate the associations of iron status at 6 years of age with dietary and other factors. Design: In a cross-sectional study, children's dietary intakes (3-day weighed food record) were recorded, body size was measured and blood samples were taken near their sixth birthday. Subjects: A sample of 188 children, from two previous studies (cohorts 1 and 2), was contacted, and 139 (74%) agreed to participate. Results: Multiple regression analyses with dietary and other factors showed that meat and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
(50 reference statements)
0
9
1
3
Order By: Relevance
“…Embora a anemia seja um dos maiores problemas mundiais de saúde pública, a média de ferro total presente na dieta de diversas regiões encontra-se acima das recomendações diárias necessárias para suprir o uso metabólico normal desse mineral, mostrando que a anemia é decorrente da baixa biodisponibilidade do ferro nos alimentos, principalmente o ferro não heme (BREITHAUPT; YAHIA; VILAZQUEZ, 2007;GUNNARSSON;THORSDOTTIR;PALSSON, 2007).…”
Section: Introductionunclassified
“…Embora a anemia seja um dos maiores problemas mundiais de saúde pública, a média de ferro total presente na dieta de diversas regiões encontra-se acima das recomendações diárias necessárias para suprir o uso metabólico normal desse mineral, mostrando que a anemia é decorrente da baixa biodisponibilidade do ferro nos alimentos, principalmente o ferro não heme (BREITHAUPT; YAHIA; VILAZQUEZ, 2007;GUNNARSSON;THORSDOTTIR;PALSSON, 2007).…”
Section: Introductionunclassified
“…Multiple regression analyses of Fe status indices and the intake of selected food items revealed that the consumption of cow's milk was almost universally negatively associated with Fe status indices at both 1 and 2 years of age, but not at 6 years of age (Table 4) (Gunnarsson et al 2006a). At 6 years of age a partial correlation of borderline significance was observed between log SF and cow's milk products (apart from cow's milk, butter and cheese; r -0 .…”
Section: Resultsmentioning
confidence: 99%
“…Iron-fortified infant formulas containing processed cow's milk can therefore be given to infants weaned before 12 months [15] or can replace breast milk when his is not available. Although cow's milk can be consumed by children older than 12 months, it is a generally poor iron source and consumption has been shown to be negatively associated with iron status [46,47] .…”
Section: Improving Non-heme Iron Absorptionmentioning
confidence: 99%